2013
DOI: 10.11604/pamj.2013.14.69.2376
|View full text |Cite
|
Sign up to set email alerts
|

Giant prostatic calculi

Abstract: Prostatic parenchymal calculi are common, usually incidental, findings on morphological examinations. They are typically asymptomatic and may be present in association with normal glands, benign prostatic hyperplasia, and prostate cancer. However giant prostatic calculi are rare. Less than 20 cases have been reported in the literature. We present the case of a 35-year-old man with two giant prostatic calculi that replaced the entire gland. He underwent an open cystolithotomy, two giant stones were removed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
2
13
0
1
Order By: Relevance
“…Thus, it is shown that the resultant intraprostatic urinary reflux and the urinary components in reflux may contribute to PCal formation [10]. Prostatic inflammatory procedures other than intraprostatic urinary reflux, dilatations occurring in prostatic asinities and after the blockage of intraprostatic channels, formation of corpora amilacea and accumulation of hydroxyapatite crystals on this and the mineralization of these with calcium are the mechanisms that can play a role in PCal formation [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is shown that the resultant intraprostatic urinary reflux and the urinary components in reflux may contribute to PCal formation [10]. Prostatic inflammatory procedures other than intraprostatic urinary reflux, dilatations occurring in prostatic asinities and after the blockage of intraprostatic channels, formation of corpora amilacea and accumulation of hydroxyapatite crystals on this and the mineralization of these with calcium are the mechanisms that can play a role in PCal formation [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Primary native calculi are usually small and multiple, and secondary calculi are usually larger [4]. Primary urethral stones can be formed from direct precipitation of elements present in prostatic secretions stasis that results from obstruction, inflammation and chronic infection of the prostate ducts [6]. They are magnesium ammonium phosphate (struvite), calcium phosphate or calcium carbonate in composition, have no nucleus and are of uniform structure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examination is usually normal but sometimes these calculations are collected on digital rectal examination as a hard nodule that was suspected more of a prostate cancer. The diagnosis of prostatic calculi is radiological standard radiographs or ultrasound especially prostate transrectal which has better diagnostic sensitivity [6]. Retrograde cystography is indicated to detect associated urethral disease [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous calcifications can be formed by the precipitation of elements present in the prostatic secretions which can result from obstruction, inflammation, and chronic infection of the ducts. However, when the stones are exogenous, they are formed from constituents of the urine, as shown by crystallographic studies of prostatic calculi [3,4].…”
Section: Discussionmentioning
confidence: 99%